A New Syndrome of Patent Foramen Ovale Inducing Vasospastic Angina and Migraine - Deepak Ravi, MD; Rushi V. Parikh, MD; Jamil Aboulhosn, MD; Jonathan M. Tobis, MD (JACC: Case Reports, 2023)
Patent foramen ovale (PFO) is the most common congenital cardiac abnormality and is usually considered a benign finding. This case series suggests a potential link between PFO and vasospastic angina. It also demonstrates PFO closure as a potential therapeutic intervention for individuals with PFO who suffer from refractory vasospastic angina. (Level of Difficulty: Intermediate.)